Respuesta :

ANSWER

The answer is B.

[tex]y = \frac{ {x}^{2} - 1}{ {x}^{2} + 2x - 3 } [/tex]

EXPLANATION

The graph represents a rational function.

This rational function has a hole at x=1 and a vertical asymptote at x=-3.

This implies that the denominator of the rational function in factored form is

[tex](x + 3)(x - 1)[/tex]

When we expand this, we get:

[tex] {x}^{2} + 2x - 3[/tex]

This tells us that the answer must be option B.

This graph also has a horizontal asymptote at y=1.

The numerator must therefore have leading term that is quadratic with the coefficient being unity or 1.

Therefore the function is actually

[tex]y = \frac{ {x}^{2} - 1}{ {x}^{2} + 2x - 3 } [/tex]